Fixed Point Theorems for Generalized θ−ϕ−Expansive Mapping in Rectangular Metric Spaces - Mohamed Rossafi; Abdelkarim Kari; El Miloudi Marhrani; Mohamed Aamri (Abstract and Applied Analysis)
In this paper, we present the notion of θ−ϕ−expansive mapping in complete rectangular metric spaces and study various fixed point theorems for such mappings. The presented theorems extend, generalize, and improve many existing results in the literature.